Los proyectos intelectuales de la izquierda en América Latina: hacia un nuevo compromiso racionalista - Torres, Esteban (SocietàMutamentoPolitica, 2018)
With few exceptions, the political and theoretical practice of the Left continues to deteriorate in Latin America from the proliferation of a new-born irrationalism. The first challenge is to try to understand the course of this community based on its most determining element: theoretical practice. Here I will initially deal with contextualizing the problem using the notion of “Intellectual Project” and to account for the transformation experienced in recent decades in the relationship between theoretical and political practice. The second moment corresponds to the central core of the article: I build a typology of intellectual left figures that could deploy an Intellectual Project from the academic system at some point in the contemporary history of Latin America. I define two general intellectual figures: the participatory social-cientist and the social-scientific translator. The work concludes with a proposal of synthesis and with the signaling of the main obstacles that it is necessary to overcome in order to activate from the academic system a new process of theoretical-political innovation in the constellation of the Regional Left.